1984
DOI: 10.1002/cjoc.19840020112
|View full text |Cite
|
Sign up to set email alerts
|

Chemical studies on alkaloids in the root of Acronychia oligophylebia Merr

Abstract: Nine alkaloids and β‐sitosterol were isolated from the root of Acronychia oligophylebia Merr. (Rutaceae). Among these alkaloids, five were identified as preskimmianine (2), evolitrine (5), kokusaginine (6), skimmianine (7) and maculosidine (8). The alkaloids 2, 5 and 8 were isolated from Acronychia genus for the first time. Oligophylicidine (10) and oligophylidine (4) were new bases. Oligophyline (3) and oligophylicine (9) were first found from natural source. Based on spectroscopic data, the structures of 3, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…oligophylebia (Wen-Hao et al 1984) and is the first time that they were detected in these species. However, these alkaloids are considered as precursors of furoquinoleine alkaloids (Storer et al 1972) already reported from these species.…”
Section: Uplc-hrms Dataset Evaluationmentioning
confidence: 78%
“…oligophylebia (Wen-Hao et al 1984) and is the first time that they were detected in these species. However, these alkaloids are considered as precursors of furoquinoleine alkaloids (Storer et al 1972) already reported from these species.…”
Section: Uplc-hrms Dataset Evaluationmentioning
confidence: 78%